2019
DOI: 10.1017/s0022215119002445
|View full text |Cite
|
Sign up to set email alerts
|

The effects of everted or inverted edges on healing of traumatic-induced tympanic membrane perforations

Abstract: ObjectivesTo evaluate the healing and hearing outcomes related to the everted or inverted edge area on slap- and fist-induced large tympanic membrane perforations.MethodsA total of 120 patients with slap- or fist-induced tympanic membrane perforations, with inverted or everted edges, affecting 50–75 per cent of the entire tympanic membrane, were randomly divided into 2 groups: an edge approximation group and a spontaneous healing group. The edge approximation group was divided into subgroups A and B based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Multiple publications evaluated the use of gelatin‐containing material, which included the terms gelatin sponge, gelatin film, and Gelfoam/Gelfilm (Pfizer, New York, NY) 12,38–46 . The sole study on gelatin film was excluded, as the tympanoplasty procedure included ossiculoplasty 47 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple publications evaluated the use of gelatin‐containing material, which included the terms gelatin sponge, gelatin film, and Gelfoam/Gelfilm (Pfizer, New York, NY) 12,38–46 . The sole study on gelatin film was excluded, as the tympanoplasty procedure included ossiculoplasty 47 .…”
Section: Resultsmentioning
confidence: 99%
“…14,37 Gelatin: Gelatin Sponge Multiple publications evaluated the use of gelatincontaining material, which included the terms gelatin sponge, gelatin film, and Gelfoam/Gelfilm (Pfizer, New York, NY). 12,[38][39][40][41][42][43][44][45][46] The sole study on gelatin film was excluded, as the tympanoplasty procedure included ossiculoplasty. 47 This resulted in a total of 511 adult and pediatric cases, in which 21.1% of perforations were grade 1, whereas the remaining 78.9% of perforations were grade 2 or higher.…”
Section: Patching Materials: Paper Patchmentioning
confidence: 99%
“…Previous study suggested that the perichondrium overlaying the epithelial layer of double layer graft and everted edges of traumatic perforation didn't induce the iatrogenic cholesteatoma. [21][22][23] On the contrary, the pearl formations were found in 5.3% patients even if the perforation margins and the squamous epithelium of TM remnant were removed completely in interlay myringoplasty with anterior subannular grafting technique for anterior and subtotal perforations. 13 In this study, 72.3% patients completed 3 years followup and performed temporal bone CT examination, CT revealed the well pneumatization of mastoids and middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional view accepted the fact that everted flaps resulted in cholesteatoma of middle ear in traumatic TM perforations (18)(19)(20)(21). But most studies do not report the incidence of cholesteatoma during the spontaneous healing process (11,(22)(23)(24)(25)(26)(27). Yamazaki et al (21) found that development of cholesteatoma in two patients with traumatic TM perforation was due to tympanoplasty sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies proved that the everted flaps gradually became necrotic and crust formation, did not develop cholesteatoma (12,(22)(23)(24)(25)(26)(27). The interplay between the middle ear and the TM keratinized epithelium is fascinating.…”
Section: Discussionmentioning
confidence: 99%